American assassin - Cuesta, Michael, 1963-; O'Brien, Dylan, 1991-; Keaton, Michael, 1951-; Lathan, Sanaa; Flynn, Vince, 1966-2013 (Santa Monica, California : Lionsgate, 2017)
After Mitch Rapp is recruited for a CIA Black Ops mission, he and his instructor are sent on a mission to uncover the truth behind a wave of seemingly random attacks.
Originally released as a motion picture in 2017.
Based on the novel by Vince Flynn.
Dolby digital 5.1, wide screen 1.85:1.
Features: Alamo Drafthouse Q & A.
Dylan O'Brien, Michael Keaton, Sanaa Lathan, Shiva Negar, Taylor Kitsch.
MPAA rating: R.
Keywords: Rapp, Mitch -- (Fictitious character) -- Drama; Flynn, Vince, -- 1966-2013 -- Film adaptations; United States. -- Central Intelligence Agency -- Drama; Assassins -- Drama; Action and adventure films; Thrillers (Motion picture); Fiction films; Video recordings for the hearing impaired; Based on the book; Feature films